Complete giant liver cell transformation with an unusual good clinical and histological course - Mohamad Adat; Sadikin Darmawan; A. H. Markum (Paediatrica Indonesiana, 1973)
A form of hepatitis occurring in the neonatal period and clinically simulating biliary atresia was first described by Craig and Landing in1952. The characteristic histopathologic feature of the disease at biopsy and autopsy was the presence of multinucleated giant liver cells replacing most of the parenchyma. The general architecture of the liver lobule however was preserved, the portal triads and central veins were in their usual places. Because of these characteristic giant cells, the disease iscalled giant cell hepatitis, giant liver cell transformation, sometimes also neonatal hepatitis, because it was thought to occur only in neonates.